2018
DOI: 10.4149/bll_2017_136
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac telocytes as principal interstitial cells for myocardial reparation and regeneration after infarction – our hope

Abstract: According to our knowledge, this is the first research experiment that focuses on the study of the distribution of c-kit positive cells at the sites of myocardial infarction in human hearts (Fig. 3, Ref. 16).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In terms of the physiological growth of the heart and the effects of exercise, most research focused solely on cardiomyocytes, while exercise is also effective in stimulating healthy heart growth on other types of heart cells [ 42 , 43 ]. Among these cells are the lesser known telocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the physiological growth of the heart and the effects of exercise, most research focused solely on cardiomyocytes, while exercise is also effective in stimulating healthy heart growth on other types of heart cells [ 42 , 43 ]. Among these cells are the lesser known telocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a decrease in the number of cardiac telocytes in the infarcted zone following myocardial infarction [ 22 , 42 , 43 , 49 , 51 ] and transplantation of telocytes to the heart with myocardial infarction reduces the size of the infarction and improves myocardial function [ 3 , 22 , 42 , 43 , 50 , 51 ]. Cardiac telocytes also help regenerate the heart’s interstitial network and maintain myocardial function, which can be important in providing the right microenvironment for the migration and development of heart stem cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of telocytes in myocardial regeneration in humans (in contrast to animal models) remains questionable. Although telocyte numbers were shown to be reduced in end-stage failing hearts [46], in our previous study we found no link between telocyte numbers and the dynamics of the reparative mechanisms in the human heart after myocardial infarction [47].…”
Section: Telocytes As Principal Cells Of Diverse Organs Of the Hummentioning
confidence: 90%
“…Multiple studies have demonstrated that the normal function and morphology of cardiac TCs are severely disrupted during myocardial infarction [45,49,50]. At first glance, this finding is not very surprising, given that the myocardial ischemia, with subsequent apoptosis, necrosis, and overall derangement of the cellular microenvironment, alters all the cell populations in the affected site, including TCs.…”
Section: Myocardial Infarctionmentioning
confidence: 99%